О распространении жуков-мягкотелок (Coleoptera, Cantharididae) на правобережной Украине - Истомина, Л.П. (Вестник зоологии, 1970)
As a result of processing the data of collections and literature it was established that 49 species of soldier beetles are found out at the territory of Right-bank Ukraine, 13 species of them are mentioned for the first time. An analysis of Cantharidae distribution on the landscape-climatic zones and subzones of the investigated region showed the forest and forest-steppe zones, where 40 species were found, to be the richest in the species. In the steppe regions the quantity of Cantharidae species and their number decrease. Cantharts livida var. rufipes is the mass species at the whole territory of the right-bank Ukraine as a whole the ratio of the dominating species in the zones is different. In zoogeographical respect the representatives of the European group dominate, amounting to 75%, transpalearcts account for 17%. The Mediterranean and steppe Cantharidae are presented by the greatest number of species.